(untitled) (International Journal of Studies in Nursing, 2022)
Idiopathic scoliosis is commonly found in adolescents of 10 to 17 years of age, patients are required to undergo various types of treatment based on different angles in scoliosis. With the summarized literature and expert opinions, this article describes the treatment and nursing care for various degrees of scoliosis.